2021
DOI: 10.1039/d0tb02983a
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial biomaterials in bone tissue engineering

Abstract: Bone infection is a devastating disease with recurrent, drug-resistant, and high morbidity features, that have prompted clinicians and scientists to develop novel approaches to combat it. Currently, although numerous biomaterials...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 213 publications
1
41
0
Order By: Relevance
“…in plant extract which synergistically interfering in more efficiently way with bacterial cell wall and shows more effect on cellular interaction leading to cell death. 30,57–62 These results show that Ag NPs exhibit potential antimicrobial activity and food preservation activity, even at low concentration.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…in plant extract which synergistically interfering in more efficiently way with bacterial cell wall and shows more effect on cellular interaction leading to cell death. 30,57–62 These results show that Ag NPs exhibit potential antimicrobial activity and food preservation activity, even at low concentration.…”
Section: Resultsmentioning
confidence: 76%
“… 29 However, recent interest on Ag NPs has particularly focused on the increasing threat of antibiotic resistance due to the excessive use/abuse of antibiotics. 30 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the biotoxicity of copper-based biomaterials should be evaluated before it is used in bone tissue engineering. It has been demonstrated that the toxicity of copper-based biomaterials is reduced by optimizing copper doping concentration, releasing curve or reducing metal particle size ( Chen et al, 2021 ). At the same time, biocompatibility and antibacterial ability must also be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an alternative is urgently needed to avoid the short life cycles of antibiotic-eluting devices and provide the implants with a lasting antibacterial effect. In light of this, the inherent antibacterial properties of some implant materials have gained increasing attention from researchers ( Tran et al, 2015 ; Xu et al, 2016 ; Bee et al, 2021 ; Calabrese et al, 2021 ; Chen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%